2009
DOI: 10.1007/s00199-009-0455-z
|View full text |Cite
|
Sign up to set email alerts
|

Hedonic price equilibria, stable matching, and optimal transport: equivalence, topology, and uniqueness

Abstract: Hedonic price equilibrium, Matching, Optimal transportation, Spence-Mirrlees condition, Monge–Kantorovich, Twist condition, C62, C78, D50,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
145
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 178 publications
(147 citation statements)
references
References 28 publications
2
145
0
Order By: Relevance
“…Speci cally, both here and in Jerez (2014), we adopt the linear programming approach used by Shapley (1955), Shapley and Shubik (1972), and Grestky, Zame (1992, 1999) to study frictionless matching models with transferable utility. (See also more recent work by Chiappori, McCann, and Nesheim (2010) and Dizdar (2015), among others). Speci cally, we show that constrained e cient allocations can be determined as solutions to a linear programming (LP) problem, whereas the hedonic wage function supporting these allocations and the associated expected payo s for workers and rms correspond to the solutions of the dual of that linear program.…”
Section: Introductionmentioning
confidence: 87%
“…Speci cally, both here and in Jerez (2014), we adopt the linear programming approach used by Shapley (1955), Shapley and Shubik (1972), and Grestky, Zame (1992, 1999) to study frictionless matching models with transferable utility. (See also more recent work by Chiappori, McCann, and Nesheim (2010) and Dizdar (2015), among others). Speci cally, we show that constrained e cient allocations can be determined as solutions to a linear programming (LP) problem, whereas the hedonic wage function supporting these allocations and the associated expected payo s for workers and rms correspond to the solutions of the dual of that linear program.…”
Section: Introductionmentioning
confidence: 87%
“…This direction has been explored by Ekeland ([Eke05, Eke10]), and later by Chiappori, McCann, and Nesheim ( [CMN10]). Figalli, Kim, and McCann have also shown that the problem becomes a convex screening problem, under a strengthening of the (A3w) condition, often known as "non-negative cross curvature" in the optimal transport literature (see [FKM11]).…”
Section: 2mentioning
confidence: 99%
“…We refer to [2], [3], [4], [6], [21], [22], [23] and the surveys and books [1], [13], [25] and [26]. It has many applications, for example in economics (matching problems), [5], [7], [8], [9], [10], [11], [20]. Closely related to this article is the case in which the involved measures are concentrated in a small strip around the boundary of a fixed domain.…”
Section: 2mentioning
confidence: 99%